Relationship between MR Imaging and Histopathologic Findings of the Brain in Extremely Sick Preterm Infants - Felderhoff-Mueser, Ursula; Rutherford, Mary A.; Squier, Waney V.; Cox, Philip; Maalouf, Elia F.; Counsell, Serena J.; Bydder, Graeme M.; Edwards, A. David (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: MR imaging can now be used safely in extremely preterm infants. The aim of this study was to compare the MR imaging appearance of the immature brain with neuropathologic findings at postmortem examination.METHODS: Seven extremely sick preterm infants, born at a median of 24 weeks' gestation, were studied using T1- and T2-weighted MR sequences. Infants died at a median of 3 days after initial MR imaging, and postmortem examinations were carried out.RESULTS: The cortex and germinal matrix were seen as areas of low signal intensity on T2-weighted images, which corresponded to their highly cellular histologic appearance. The periventricular and subcortical layers of white matter had a high signal intensity, corresponding to high fiber and relatively low cellular density; the intermediate layer of low signal intensity corresponded to a dense band of migrating cells. Regions of acute hemorrhage were seen as low signal intensity and regions of infarction as high signal intensity on T2-weighted images. One infant with mild periventricular leukomalacia had some low signal intensity on T1-weighted images, but no focal changes on T2-weighted images. Regions of neuronal mineralization, seen in association with infarction and capillary proliferation, within the basal ganglia and thalami were characterized by very low signal intensity on T2-weighted images and by very high signal intensity on T1-weighted images. There were no imaging abnormalities detected in regions with more subtle histologic abnormalities, such as increased glial or apoptotic cells.CONCLUSION: MR imaging can be used to observe normal developing brain anatomy in extremely premature infants; it can detect areas of hemorrhage and infarction within the developing brain, but conventional MR imaging may not detect more subtle histologic abnormalities.